Complexity of Viral Epitope Surfaces as Evasive Targets for Vaccines and Therapeutic Antibodies - Miller, Nathaniel L.; Raman, Rahul; Clark, Thomas; Sasisekharan, Ram (Frontiers in Immunology, 2022)
The dynamic interplay between virus and host plays out across many interacting surfaces as virus and host evolve continually in response to one another. Viral surface proteins are typically the immunodominant antigens that are targeted for antibody-mediated neutralization by the host’s humoral immune response. In particular, epitope-paratope interactions (EPIs) between viral antigen and host antibodies drive much of this evolutionary race. In this review, we describe a series of recent studies examining aspects of epitope complexity that go beyond two interacting protein surfaces as EPIs are typically understood. To structure our discussion, we present a framework for understanding epitope complexity as a spectrum along a series of axes, focusing primarily on 1) epitope biochemical complexity (e.g., epitopes involving N-glycans) and 2) antigen conformational / dynamic complexity (e.g., epitopes with differential properties depending on antigen state or fold-axis). We highlight additional epitope complexity factors including epitope tertiary/quaternary structure, which contribute to epistatic relationships between epitope residues within- or adjacent-to a given epitope, as well as epitope overlap resulting from polyclonal antibody responses, which is relevant when assessing antigenic pressure against a given epitope. Finally, we discuss how these different forms of epitope complexity can limit EPI analyses and therapeutic antibody development, as well as recent efforts to overcome these limitations.